(untitled) - Nehru, Jawahrlal (New York, 1962)
Glimpses of World History, a book written by Jawaharlal Nehru in 1934, is a panoramic sweep of the history of humankind. It is a collection of 196 letters written between 1930-1933, as an introduction to the world history to his daughter Indira, then thirteen years old. The letters, written in a span of thirty months when Nehru was imprisoned in various places by the British, starts off with one he sends to his daughter on her birthday.
Keywords: World history,Lịch sử thế giới